Prevenção do tabagismo e o papel das escolas: um estudo exploratório em uma escola pública - (:unkn) unknown (Universidade Federal do Pampa, 2018)
Smoking prevention can occur in school, as public health policies affirm that the school is a privileged space for the development of preventive, preventive and health education actions. Thus, the purpose of this article was to investigate whether the Public School State Institute of Education Dr. Carlos Vidal de Oliveira, Sant'Ana do Livramento-RS has actions to prevent smoking and to understand the role of the school in front of the implementation of control programs . The research is characterized as applied research, exploratory, descriptive and case study. Data collection was done through in-depth interviews with the Institute's teachers. The results showed the teachers' perception of the role of the school in relation to smoking control, the interviewees pointed out that the school has the role of clarifying, commenting, guiding, talking about the subject, always putting on alert about the evil of consuming tobacco, emphasizing the importance of smoking prevention. The data also show that the school does an informative work on the subject when a related problem arises, not carrying out preventive and educational work.
Prevention of smoking and the role of schools: an exploratory study in a public school
Keywords: Gestão pública; Prevenção ao tabagismo; Escola pública; Public administration; Prevention of smoking; Public school; CNPQ::CIENCIAS SOCIAIS APLICADAS